Medieval Nonsense Signifying Nothing in Fourteenth-Century England - Kirk, Jordan (Fordham series in medieval studies., 2021)
"In a series of close and unorthodox readings of works by Priscian, Boethius, Augustine, Walter Burley, Geoffrey Chaucer, and the anonymous authors of the Cloud of Unknowing and St. Erkenwald, Jordan Kirk reveals the way that writers across the fourteenth century reckoned with the word as mere sound. Medieval Nonsense rebuts the idea that single-minded devotion to the kernel of meaning within the word motivated these authors in their engagement with vox sola, the mere utterance. Rather, they recognized the possibilities inherent in the accounts of language transmitted to them from antiquity, and they transformed those accounts into new ideas, forms, and practices of nonsignification"--